Exploring the relationship between teachers' perceptions of cultural responsiveness, student risk, and classroom behavior. Issue 10 (3rd June 2021) - Fallon, Lindsay M.; Veiga, Margarida B.; Susilo, Annisha; Robinson‐Link, Patrick; Berkman, Talia S.; Minami, Takuya; Kilgus, Stephen P.
Abstract: It is important to explore the relationship between teachers' perceptions of their cultural responsiveness as well as students' classroom behavior and risk, as these relationships may impact decisions about equitable access to school behavioral health supports. This paper includes two studies conducted with teachers in two large suburban school districts. Study 1 investigated the relationship between teachers' ( n  = 20) ratings on a measure of cultural responsiveness, the Assessment of Culturally and Contextually Relevant Supports (ACCReS), and students' classroom behavior. Results indicated that higher ACCReS scores significantly predicted lower classwide disruptive behavior. Study 2 investigated the relationship between teachers' ( n  = 30) ratings on the ACCReS and ratings of their students' risk on the Social, Academic, and Emotional Behavior Risk Screener . For social behavior, higher ACCReS scores predicted teachers perceiving lower social risk; however, identification as a Black student and a student with a disability predicted higher risk. Findings are preliminary, yet implications include recommendations for high‐quality professional development to promote teacher cultural responsiveness. Such support could guide teachers to create educational environments in which fewer discipline referrals for behavior occur, teachers perceive less social risk, and access to school behavior supports is more equitable.